2018
DOI: 10.1016/j.matchar.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature transmission Kikuchi diffraction in the SEM

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…• The quality of Kikuchi pattern features is influenced by temperature effects [46] such as increased thermal vibrations.…”
mentioning
confidence: 99%
“…• The quality of Kikuchi pattern features is influenced by temperature effects [46] such as increased thermal vibrations.…”
mentioning
confidence: 99%
“…Recent investigations on the depth resolution of on-axis TKD [11] and on the range of diffraction contrast depending on sample and microscope parameters for on-axis TKD have been presented [12]. Furthermore, due to enhanced signal and speed, it was also shown that this configuration might be more beneficial for dynamic TKD investigation [13] and can also be advantageous for non-conductive samples and weakly diffracting materials.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Finally, the requirement of the on-axis TKD detector movement between the two positions makes it impossible to acquire an orientation map and high-quality BF/DF images simultaneously. As previously pointed out [13], this limitation can be very critical in dynamic investigations, first because STEM images can be acquired much faster than TKD measurements, and second because in many situations the imaging-mapping combination is essential for a thorough understanding of the dynamic evolution of the microstructure.…”
Section: Accepted Manuscript Distances With and Without Immersion Mode (Sample Immersed In Magnetic Field) (Single Column)mentioning
confidence: 99%
“…Recently, TKD was optimized by changing the geometric configuration from a conventional off-axis to an on-axis detector geometry, which improves the lateral resolution, acquisition speed, and pattern quality (Fundenberger et al, 2015, 2016; Brodu et al, 2017; Yuan et al, 2017). However, as the source of TKD patterns is at the exit surface of the sample, the film surface has a strong influence on the quality of the patterns and thus the reliability of the maps (Keller & Geiss, 2012; Sneddon et al, 2016; Fanta et al, 2018; Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%